E-LEARNING PADA SMKS 4 PUTRA NUSANTARA BERBASIS LEARNING MANAGEMENT SYSTEM (LMS) MOODLE - Herita Apriati; indra kanedi; Ricky Zulfiandry (UNIVED Press, 2022)
Abstract Support for internet network infrastructure at the Putra Nusantara S-4 Vocational High School triggers the development of service facilities for students. One alternative is the development of an e-learning system in an effort to improve online learning through the delivery of learning materials, discussions, and other lecture activities conducted through electronic media. The aim of this research is to create e-learning at the Putra Nusantara S-4 Vocational High School using the Moodle Learning Management System (LMS). The research method used in this study is the waterfall method with the stages of analyzing the old system, analyzing the new system, designing the system, implementing the system and testing the system. The results of the e-learning made are in the form of a Moodle-based learning application. E-learning displays subject matter in various application file formats in accordance with existing subjects in the competence of food crop agribusiness expertise, online assignments by teachers to students, online discussions through in-app forums and exams (quizzes). carried out by teachers for their students (students) in an effort to improve the professionalism of teacher competencies and student competencies in agriculture. Keywords: E-learning, Moodle, PHP,